Factors affecting the utilization of the java health centre information system (JHCIS) by the primary care units staffs at Nongkhai province - Thiangtrong, et al., Patama; Bouphan, Prachak (Asia-Pacific Journal of Science and Technology, 2017)
This research was based on cross-sectional descriptive research. Its objective was to investigate factors influencing the use of Java health center information systems (JHCIS) by the staffs of primary care units at Nongkhai province. The population of this study was 135 public health officers of the health center located in Nongkhai province and 76 subjects were drawn as the subjects of this study by systematic random sampling. The data were collected by the developed questionnaire, which was verified by three experts. Its validity was tested and gained coefficient Cronbach’s alpha 0.97. The collected data were analyzed by a computer package program and statistically disseminated by percentage, mean, standard deviation, median, Pearson’s coefficient and multi-stage regression analysis. It was revealed that the overall using of JHCIS by the staffs of primary care units at Nongkhai province was in high level with 3.93 (S.D.=0.54). Furthermore, four factors could predict the use of the java health center information systems JHCIS by the staffs of primary care units at Nongkhai province include the management and the budget of the organizational supports, the recognition and interpersonal-relationship of the motivation and hygiene factors with a level significance (68.50%).